Hydrodynamic Controls on Seasonal Circulation Modes and Sediment Convergence in a Monsoon-Driven Asymmetric Inlet - Nguyen Quang Duc Anh; Nguyen Truong Duy; Hitoshi Tanaka; Tran Thanh Tung (Journal of Marine Science and Engineering, 2026)
Tam Quan Inlet, a monsoon-driven asymmetric entrance on the south-central coast of Vietnam, has experienced persistent shoaling and severe downdrift erosion despite jetty construction and repeated maintenance dredging. This study investigates the unresolved linkage between seasonal circulation reorganization, inlet-directed sediment convergence, channel infilling, and southern-beach erosion. A coupled Delft3D-FLOW/WAVE model, constrained by field observations from May 2022 and November–December 2022, was used to diagnose hydrodynamic controls and compare alternative management layouts. The model satisfactorily reproduced the dominant variability of water level, wave conditions, and depth-averaged currents during calibration and independent validation, providing a suitable basis for process diagnosis and comparative layout assessment. The simulations identify four recurrent circulation modes: a cape-crossing north-to-south longshore jet, flow acceleration and deflection near the southern jetty, a northeast-monsoon recirculation cell that promotes inlet-directed convergence from the southern beach, and a partial summer reversal under SE-sector waves. These modes explain why shoaling persists after one-sided intervention and why the southern shoreline functions simultaneously as an eroding downdrift beach and a seasonal sediment source to the inlet. Among the tested layouts, PA2 most effectively concentrates flow through the inner throat while relocating sediment retention to an external storage basin, supporting controlled trapping and periodic bypassing. The results support a sediment-balanced management strategy that integrates controlled trapping, maintenance dredging, and sediment bypassing to improve navigation reliability and reduce the sediment deficit along the downdrift shoreline.